Social vulnerability associated with sanitation and its connection to environmental injustice in the West Bank and Gaza Strip in Palestine - Rammal, Fuad Yousef; Alkhazzan, Bouchta (Journal of Humanities & Social Sciences, 2022)
This paper aimed to discuss the concept of social vulnerability associated with sanitation and its connection to environmental injustice in a framework of governance as a new way to manage natural resources, which includes the participation of social actors in planning environmental policies, by investigating how the social vulnerability associated with sanitation and its connection to environmental injustice in the West Bank and the Gaza Strip in Palestine, and the paper analyzes cases of inequality within two axes. The first axis is based on the use of the methodology of organizing information that is carried out through bibliographic review, and the second axis is based on the statistical analysis of the relevant tables, which showed an increasing mathematical function by increasing independent variables that are closely related, noting that The results of the analysis showed a close and increasing correlation between the method of connecting wastewater to the sewage networks with poverty rates based on the area of ​​residence (rural, camp, urban). The analysis focuses on the two axes of the paper on taking into account the essential role of public policies in combating social and environmental inequalities, especially those related to the arbitrary practices of the Israeli occupation. One of the most important results of the analysis was that the social vulnerability associated with sanitation is related to environmental injustice in the West Bank and Gaza Strip, and is exacerbated by the arbitrary practices of the Israeli occupation, especially environmental ones. The paper concluded with the importance of taking into account the integration of water policies with those related to agriculture and economic works, and the inclusion of all socio-economic factors within specialized programs within the framework of partnership with institutions, including private sector institutions, to develop joint activities between them, and to prioritize safe environmental sanitation for the poor population, and areas Low-income people and those most affected by the arbitrary policies of the Israeli occupation, in addition the paper recommended the importance of establishing programs to ensure social justice, combat differences in service levels, adopt the principle of differentiation between users by imposing fees on water uses, and manage the balance between preserving resources and promoting multiple uses for them.